Comparison of the Pharmacological Effects of Paricalcitol and Doxercalciferol on the Factors Involved in Mineral Homeostasis - J. Ruth Wu-Wong; Masaki Nakane; Gerard D. Gagne; Kristin A. Brooks; William T. Noonan (International Journal of Endocrinology)
Vitamin D receptor agonists (VDRAs) directly suppress parathyroid hormone (PTH) mRNA expression. Different VDRAs are known to have differential effects on serum calcium (Ca), which may also affect serum PTH levels since serum Ca regulates PTH secretion mediated by the Ca-sensing receptor (CaSR). In this study, we compared the effects of paricalcitol and doxercalciferol on regulating serum Ca and PTH, and also the expression of PTH, VDR, and CaSR mRNA. The 5/6 nephrectomized (NX) Sprague-Dawley rats on a normal or hyperphosphatemia-inducing diet were treated with vehicle, paricalcitol, or doxercalciferol for two weeks. Both drugs at the tested doses (0.042–0.33 𝜇g/kg) suppressed PTH mRNA expression and serum PTH effectively in the 5/6 NX rats, but paricalcitol was less potent in raising serum Ca than doxercalciferol. In pig parathyroid cells, paricalcitol and the active form of doxercalciferol induced VDR translocation from the cytoplasm into the nucleus, suppressed PTH mRNA expression and inhibited cell proliferation in a similar manner, although paricalcitol induced the expression of CaSR mRNA more effectively. The multiple effects of VDRAs on modulating serum Ca, parathyroid cell proliferation, and the expression of CaSR and PTH mRNA reflect the complex involvement of the vitamin D axis in regulating the mineral homeostasis system.